PENGATURAN PENGAWASAN LALU LINTAS BARANG KENA CUKAI PADA KAWASAN PERDAGANGAN BEBAS (Studi Pencabutan Fasilitas Cukai Pada Kawasan Perdagangan Bebas) - Budiman, Arif (UNES Law Review, 2021)
Based on Article 17 section (2) of Government Regulation Number 10 of 2012 Excisable Goods in Free Trade Zone (FTZ) can be granted exemption. However, after the issuance of Government Regulation Number 41 of 2021 the duty-free facility is revoked, the Excisable Goods in FTZ is charged to excise duty. Formulation of the problem in this thesis is how to regulate and supervise the excisable goods traffic at the FTZ and how to implicate the juridical of the official note issued by the Director General of Customs and Excise regarding the Revocation of Duty-Free Facilities at the FTZ. This is a legal research with descriptive specifications. The approach used is a normative juridical approach. It is used secondary data collected through literature research and analyzed the data qualitatively to be presented in a qualitative descriptive form. Based on the results of the study, it is known that the Regulation of the Traffic of Excisable Goods at the FTZ in Indonesia before the Memorandum of the Directorate General of Customs and Excise number 466/BC/2019 used the CK-FTZ document. Following the Government Regulation Number 41 of 2021, the arrangement was the same as the excise document in other customs areas. The supervision of the traffic of excisable goods at the FTZ in Indonesia carried out by DJBC is a form of prevention and repressive (action). The Juridical Implications of the Official Memorandum number ND-466/BC/2019 revoke the duty-free facility at the FTZ indirectly. Government Regulation Number 41 of 2021 has been issued to answer the Official Memorandum, but it is necessary to review it if it is related to the above regulation, Law Number 44 of 2007 so that in the formation of a legislation in accordance with the hierarchy and in line "lex superior" principle. derogat legi inferior".